2017
DOI: 10.1021/acsphotonics.7b00305
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Third-Harmonic Generation from Polaritons in the Ultrastrong Coupling Regime

Abstract: Strong inter-particle interactions between polaritons have traditionally stemmed from their exciton component. In this work, we impart a strong photonic nonlinearity to a polaritonic mode by embedding a nonlinear polymethine dye within a high-Q all-metal microcavity. We demonstrate nonlinear microcavities operating in the ultrastrong coupling regime with a normalized coupling ratio of 62%, the highest reported to date. When pumping the lower polariton branch, we observe tunable third-harmonic generation spanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
104
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 39 publications
9
104
1
Order By: Relevance
“…There are several widely-used technologies that ultimately base their efficiency on the rates of chemical reactions or electron transfer processes that occur in excited electronic states (e.g., sunscreens, polymers, catalysis, solar cells, OLEDs). Therefore, the ability to manipulate the rates and branching ratios of these fundamental chemical processes in a reversible manner using light-matter interaction with a vacuum field, suggests a promising route for targeted control of excited state reactivity, without exposing fragile molecular species or materials to ESC Cavity-enhanced energy transfer and conductivity in organic media [30,[137][138][139] ESC/VSC Strong coupling with biological light-harvesting systems [44,[140][141][142] ESC Cavity-modified photoisomerization and intersystem crossing [28,104,[143][144][145] ESC Strong coupling with an individual molecule in a plasmonic nanocavity [95,96,98,146] ESC Polariton-enhanced organic light emitting devices [32,35,147,148] EUSC Ultrastrong light-matter interaction with molecular ensembles [29,36,92,147,[149][150][151] VSC/VUSC Vibrational polaritons in solid phase and liquid phase Fabry-Perot cavities [38-40, 45-47, 49-54, 152] VSC Manipulation of chemical reactivity in the ground electronic state [43,55,153] ESC Cavity-controlled intramolecular electron transfer in molecular ensembles. [134,[154][155]…”
Section: A Recent Experimental Progressmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several widely-used technologies that ultimately base their efficiency on the rates of chemical reactions or electron transfer processes that occur in excited electronic states (e.g., sunscreens, polymers, catalysis, solar cells, OLEDs). Therefore, the ability to manipulate the rates and branching ratios of these fundamental chemical processes in a reversible manner using light-matter interaction with a vacuum field, suggests a promising route for targeted control of excited state reactivity, without exposing fragile molecular species or materials to ESC Cavity-enhanced energy transfer and conductivity in organic media [30,[137][138][139] ESC/VSC Strong coupling with biological light-harvesting systems [44,[140][141][142] ESC Cavity-modified photoisomerization and intersystem crossing [28,104,[143][144][145] ESC Strong coupling with an individual molecule in a plasmonic nanocavity [95,96,98,146] ESC Polariton-enhanced organic light emitting devices [32,35,147,148] EUSC Ultrastrong light-matter interaction with molecular ensembles [29,36,92,147,[149][150][151] VSC/VUSC Vibrational polaritons in solid phase and liquid phase Fabry-Perot cavities [38-40, 45-47, 49-54, 152] VSC Manipulation of chemical reactivity in the ground electronic state [43,55,153] ESC Cavity-controlled intramolecular electron transfer in molecular ensembles. [134,[154][155]…”
Section: A Recent Experimental Progressmentioning
confidence: 99%
“…In recent years, several experimental groups have used a diverse set of photonic structures to establish the possibility of manipulating intrinsic properties of molecules and molecular materials under conditions of strong and ultrastrong light-matter coupling with a confined electromagnetic vacuum in the optical [28][29][30][31][32][33][34][35][36][37] and infrared [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] regimes. This growing body of experimental results have positioned molecular cavity systems as novel implementations of cavity QED that complement other physical platforms with atomic gases [57], quantum dots [58], quantum wells [59], or superconducting circuits [60].…”
Section: Introductionmentioning
confidence: 99%
“…Polaritonic chemistry has become an emerging research field, aimed at providing new tools for the fundamental investigation of light-matter interaction. Since the pioneering experimental work carried out by the group of Ebbesen, in which they observed that strong light-matter coupling could modify chemical landscapes [8], the field of 'molecular polaritons' experienced much activity from both experimental [9][10][11][12][13][14][15][16][17][18][19] and theoretical [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] research groups. Recent achievements on molecules strongly coupled to a cavity mode, such as that strong cavity-matter coupling can alter chemical reactivity [9,38], provide long-range energy or charge transfer mechanisms [12,37], modify nonradiative relaxation pathways through collective effects [35], and modify the optical response of molecules [31,40], support the relevance of such a new chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…25 Since the mixed light-matter states have different PESs than unmixed states, the strong light-matter interaction offers an attractive way to drive a chemical reaction toward a desired product by reshaping the PES landscape. This possibility inspired the appearance of polaritonic chemistry aiming to manipulate chemical structure and reactions via the formation of hybrid light-matter states (polaritons), which has become a topic of intense experimental [26][27][28] and theoretical research [29][30][31][32][33][34] in the past few years. In addition, recent developments have found that vibrational strong coupling (VSC) can resonantly enhance thermally-activated chemical reactions via the formation of vibrational polaritons.…”
Section: Introductionmentioning
confidence: 99%